Genito-urinary genomics and emerging biomarkers for immunomodulatory cancer treatment. (October 2018) - Gevaert, Thomas; Montironi, Rodolfo; Lopez-Beltran, Antonio; Van Leenders, Geert; Allory, Yves; De Ridder, Dirk; Claessens, Frank; Kockx, Mark; Akand, Murat; Joniau, Steven; Netto, George; Libbrecht, Louis
Abstract: Immunotherapy is gradually becoming a key factor in the therapeutic algorithm for patients with genito-urinary (GU) cancers at different stages of disease. Robust and reliable biomarkers are crucial for an appropriate inclusion of patients in clinical trials and for a reliable patient selection for treatments with immunomodulatory drugs. The increasing knowledge on the genomic landscape of GU cancers supports stratification of patients for targeted therapies. This review focusses on emerging biomarkers and the role of genomics in predicting clinical benefit to immunomodulatory agents in GU cancers. Based on cancer incidences and available data we restricted this overview to bladder, prostate and renal cancer.